The The Characteristics of Resilient Organizations within Crisis Management: A general review of the Sultanate of Oman’s response to Cyclone Shaheen during October 2021 - Almufarji, Mohamed; Husin, NOR AZILAH (Archives of Business Research, 2022)
Purpose: This paper examines crisis management literature, and historical rare events, alongside a recent rare event. The purpose of the paper is to ask whether we, as an industry, are achieving the resilience that technology and changing societies require, and are those societies responding effectively to the challenge of the diversity of this century’s global organizational resilience factor needs, of which climate change is just one. The paper seeks to facilitate a wider understanding of the organizational resilience, institutional, and individual limitations, and failures, contributing to those rare events. Originality: It is clear that with each decade, each generation, a lack of imagination appears to have corrupted institutional, organizational, and management responses. During this original literary presentation, in each situation, whether man-made or natural, greater imagination or foresight in the application of resilience processes may not have prevented the event, however, they would almost without exception have mitigated the losses. Approach: Presenting these events in this manner offers real, relatable situations, and should therefore be more contextual to the reality and purpose of resilience as an organizational quality. Although the exercise may appear simplistic, simplicity should not be confused with the clarity and candor of an inquiry-based learning implementation where the research is adapted to respond to its contemporary environment and is encouraged by a dearth of plain-speaking analysis of contemporary responses. Findings: This review of the reaction and response of the Oman National Emergency Management Centre to the challenges presented by Cyclone Shaheen, their preparedness, response effectiveness, and recovery… their organizational resilience.